Real-time implementation of digital filters - S Theivanai (Nanyang Technological University, 2022)
Digital filters are now more frequently utilized than analog filters due to the rising use of electronic devices and the rapid development of microprocessors. Digital filters provide more customization, cost savings, and a wide range of potential applications for the Internet of Things. Additionally, digital filters are programmable, temperature and time-stable, and can accurately handle both extreme frequency signals [3]. To observe and comprehend the effectiveness of digital filters in real-time audio signal processing, in this thesis, sample music played from YouTube is processed using a program that applies digital filters created using MATLAB's readily available filter designer tool. The audio is then analysed and played on powered speakers. The filters and digital signal processing techniques used in this project are Finite Impulse Response (FIR) equiripple Low-Pass, High-Pass, Band-Pass, and Band-Stop filters. The C application is run in real-time by the TMS320C5515 eZdsp USB Stick (DSP Stick), a moderately cost piece of accessible hardware designed for processing repeated, computationally heavy processes quickly. This project successfully illustrates the potential of amateur hardware to explore and show fundamental digital signal processing principles, despite challenges with surroundings and equipment.